An optimal indoor trust-region PPP algorithm with constrain of homologous array pseudolite. Issue 5 (1st March 2022) - Sheng, Chuanzhen; Yu, Baoguo; Zhang, Ziteng; Fan, Guangwei; Wang, Xingxing; ZiqianWu,
Abstract: Homologous array pseudolite with simple time synchronization technique can provide high-precision larger-area indoor location service with outdoor GNSS receiver, but this architecture is born with several drawbacks, such as poor geometry, larger linearization error and multi-path error caused by signal reflection, and indoor positioning with this homologous array pseudolite can easily lead to potential divergence. Besides, fluctuation of time-delay, error of phase center and potential multipath error break integer propriety of carrier phase ambiguity and can't be ignored for indoor PPP (Precise Point Positioning). Under these constrictions, optimal ambiguity-float indoor PPP algorithm with trust region is proposed, and performance of this optimal algorithm with the modified Levenberg-Marquardt technique, which is designed to avoid potential divergence particularly for poor geometry, is assessed with simulation and observation filed experiment. Meanwhile, the domain factor affecting performance of PPP and mechanism of accumulative error when moving are analyzed. The experimental result reveals that: unavoidable inaccuracy of position of pseudolite transmitting antenna can cause larger error of carrier phase bias that can be larger than 0.105 cycles, and it along with fluctuation of hardware group delay and multi-path error will cause position error that can be larger than 0.12 for most cases, the indoor static and kinematic PPP can obtain a few centimeter and smooth trace respectively, and the accuracy of indoor positioning based on this optimal algorithm can be better than 0.1668 m even at the corner of experiment area with poor geometry. Still there is particular circumstance that accuracy of this algorithm can be larger than 0.5741 m due to serious accumulative error with less satellite available when moving, the mechanism for it is analyzed with relationship between error of position and measurement error and depicted as follows: when some satellites with cycle slip occurs, the accuracy of position determined will reduce greatly due to less satellite available particularly with indoor homologous array pseudolite. Afterwards, the error of the position determined will lead to error of carrier phase ambiguity biases, which will cause large biases of subsequent position determined.